Thoracic kyphosis comparisons in adolescent female competitive field hockey players and untrained controls - Rajabi, R.; Mobarakabadi, L.; Alizadhen, H. M.; Hendrick, P. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The aim of this study was to compare the thoracic kyphosis angles of adolescent female field hockey players and non-athletes and to examine the relationship between the thoracic kyphosis and training regimes in hockey. METHODS: Seventy-four female participants including 37 field hockey players (mean age 19.03 ±1.24 years) and 37 non-athletes (mean age 18.21± 1.22) were recruited in this cross-sectional study. The hockey players met a minimum criterion of 3 years of experience in the Iranian first division female hockey league. The thoracic kyphosis degree was measured between T1-T12 using a non-invasive flexible ruler. RESULTS: A significant difference in the thoracic kyphosis degree between athletes (M=41. 71°, SD=5.38°) and non-athletes (M=36.72°, SD=6.01°); t (72)=3.76, P=0.001 was revealed. The magnitude of these differences in the means was very large (eta squared=0.016). There was a moderately positive correlation between the athletic history (number of years of hockey participation) and thoracic kyphosis, r=0.36, N.=37, P=0.031. However, the relationship between the cumulative training exposure (yearly training hours) and the degree of thoracic kyphosis was not significant. CONCLUSION: Thoracic kyhphosis was significantly increased in adolescent female field hockey players and was found to be associated with the cumulative number of years of hockey participation. These results suggest a possible association between the semi-crouched posture in field hockey and thoracic kyphosis in elite adolescent athletes The results also suggest that number of years of field hockey participation is a determinant in the increased kyphosis.